IgG4-related kidney disease - O.B. Iaremenko; D.I. Koliadenko (Počki, 2021)
IgG4-related disease (IgG4-RD) is an immune-mediated fibro-inflammatory disease characterized by the formation of sclerotic tumor-like masses with dense lymphoplasmacytic infiltrates containing a significant number of IgG4-plasma cells. IgG4-RD is characterized by a wide range of clinical manifestations since the disease can involve almost any organ. Renal damage is observed in about 15 % of patients with IgG4-RD. The article presents a review of data about clinical manifestations of IgG4-related kidney disease (IgG4-RKD), specific features of diagnosis, and modern treatment approaches. The review of scientific publications was conducted in the international electronic scientometric database PubMed using keywords “IgG4-related kidney disease”, “IgG4-RKD radiographic findings”, “IgG4-related tubulointerstitial nephritis”, “IgG4-related membranous glomerulonephritis” over the period 2012–2020. The most common renal lesions in IgG4-RD are tubulointerstitial nephritis and membranous glomerulonephritis. They occur predominantly in older males. At the time of diagnosis, patients mostly already have concomitant extrarenal manifestations of IgG4-RD (sialadenitis, pancreatitis, lymphadenopathy). The clinical picture is usually vague, although nephrotic syndrome and chronic renal failure may occur. Typical manifestations of IgG4-RKD on CT are multiple low-dense foci, thickening of the renal pelvis, diffuse kidney enlargement. Renal involvement in IgG4-RD is often accompanied by low levels of complement. Early detection and treatment of IgG4-RKD are extremely important due to the increase in morbidity and mortality due to the development of chronic kidney disease. Glucocorticoids (GC) are first-line drugs for IgG4-RD. Despite a good response to GC, even a slight delay in treatment can lead to the development of renal tissue atrophy. The use of immunosuppressive drugs is advisable in cases when the dose of GC cannot be reduced due to the constantly high activity of the disease. Rituximab (a CD20+ B-lymphocyte inhibitor) may be used in patients with a recurrent course of IgG4-RKD.